2021
DOI: 10.21037/tau-20-1163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myeloid ecotropic viral integration site (MEIS) family genes on tumor microenvironment remodeling and its potential therapeutic effect

Abstract: Background: The myeloid ecotropic viral integration site (MEIS) family of genes is related to the occurrence, development, and outcome of many cancers. However, its role in the immune and tumor microenvironment (TME) is unclear. This study explored the relationship between the expression of MEIS genes and patient survival, immune subtypes, TME, tumor stem cell correlation, and drug sensitivity in cancer. Methods: We used The Cancer Genome Atlas pan-cancer data to analyze the expression of the MEIS family genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…In prostate cancer, MEIS2 has been reported as a potential tumor suppressor . Previous study also illustrated that MEIS2 may be associated with chemoresistance and exert effect on the sensitivity or resistance of tumor cells to drug therapy and could be a therapeutic target to overcome drug resistance or enhance drug sensitivity . Our study demonstrated that MEIS2 was notably lowly expressed in prostate cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In prostate cancer, MEIS2 has been reported as a potential tumor suppressor . Previous study also illustrated that MEIS2 may be associated with chemoresistance and exert effect on the sensitivity or resistance of tumor cells to drug therapy and could be a therapeutic target to overcome drug resistance or enhance drug sensitivity . Our study demonstrated that MEIS2 was notably lowly expressed in prostate cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 64%
“…8 Previous study also illustrated that MEIS2 may be associated with chemoresistance and exert effect on the sensitivity or resistance of tumor cells to drug therapy and could be a therapeutic target to overcome drug resistance or enhance drug sensitivity. 37 Our study demonstrated that MEIS2 was notably lowly expressed in prostate cancer tissues and cells. After overexpression of MEIS2, PC-3 cell viability was notably attenuated, and the number of cells in the S phase decreased, while that in the G0/ G1 phase increased.…”
Section: Discussionmentioning
confidence: 58%
“…The constitutive NF-κB signaling circuit drives the expression of a group of stem cell transcription factors, including Twist2, Sox2, Oct4, and Nanog, to promote the cancer stem cell-like characteristics and tumorigenicity of CRPC cells [22]. Consistently, a recent report supported the role of MEIS2 in cancer cell stemness [28]. In addition, it has been reported that high mobility group box 1 protein (HMGB1) activates the NF-κB signaling pathway via interaction with and binding to TNFR1 in CRPC cells [29].…”
Section: Inflammatory Signaling In Pca Cells In Pca Castration Resistancementioning
confidence: 56%
“…This discrepancy may be caused by the small size of our sample. Additionally, the MEIS1 gene expression behavior in malignant cells is influenced by many factors, including the immune status of the patients and the tumor microenvironment [33].…”
Section: Discussionmentioning
confidence: 99%